Comparison of the effect of continuous intravenous infusion and two bolus injections of remifentanil on haemodynamic responses during anaesthesia induction: a prospective randomised single-centre study. Issue 1 (December 2016) - Maruta, Toyoaki; Kodama, Yoshihumi; Tanaka, Ishie; Shirasaka, Tetsuro; Tsuneyoshi, Isao
Abstract Background Remifentanil is an effective drug for protecting against adverse haemodynamic responses to tracheal intubation. We compared the haemodynamic responses during anaesthesia induction between continuous intravenous (IV) infusion and two bolus injections of remifentanil. Methods This prospective, randomised, open-label, single-centre study included patients with American Society of Anesthesiologists physical status I-II, scheduled to undergo elective surgery under general anaesthesia. Patients were randomised into two groups based on remifentanil administration type: the continuous IV infusion group (Group C) receiving a 0.3-μg/kg/min remifentanil infusion for 5 min followed by a 0.1-μg/kg/min remifentanil infusion, and the IV bolus group (Group B) receiving a combination of two bolus injections of remifentanil (first bolus of 0.4 μg/kg and second bolus of 0.6 μg/kg after 3 min) and 0.1 μg/kg/min remifentanil. General anaesthesia was induced with 1 mg/kg propofol and 0.6 mg/kg rocuronium 3 min after remifentanil infusion (Group C) or immediately after the first bolus of remifentanil (Group B). Tracheal intubation was performed 4 min after the injection of propofol and rocuronium. Heart rate and non-invasive blood pressure were recorded at 1-min intervals from baseline (i.e., before induction) to 5 min after tracheal intubation. Results A total of 107 patients were enrolled (Group C, 55; Group B, 52). Normotensive patients with no history of antihypertensive medication use were assigned to the normotensive subgroup (41 each in both groups), while those with hypertension but without a history of antihypertensive medication use were assigned to the untreated hypertensive subgroup (Group C vs. B, n  = 7 vs. 4). Finally, patients with a history of antihypertensive medication use were assigned to the treated hypertensive subgroup (7 each in both Groups C and B). No differences in heart rate and blood pressure were observed between Groups C and B within each subgroup. Conclusions Haemodynamic responses during anaesthesia induction were similar between continuous infusion and two bolus injections of remifentanil within both normotensive and hypertensive patients with or without medication. Trial registration The trial was retrospectively registered with Japanese Clinical Trial Registry "UMIN-CTR" on 20 October 2016 and was given a trial ID numberUMIN000024495 .